Crystal structure and hydrogen storage properties of AB-type TiZrNbCrFeNi high-entropy alloy. (29th April 2023) - Andrade, Gaspar; Zepon, Guilherme; Edalati, Kaveh; Mohammadi, Abbas; Ma, Zhongliang; Li, Hai-Wen; Floriano, Ricardo
Abstract: The crystal structure and hydrogen storage properties of a novel equiatomic TiZrNbCrFeNi high-entropy alloy (HEA) were studied. The alloy, which had an AB-type configuration ( A: elements forming hydride, B: elements with low chemical affinity with hydrogen ), was selected with the aid of thermodynamic calculations employed by the CALPHAD method. The arc-melted AB-type TiZrNbCrFeNi alloy showed the presence of two C14 Laves phases in different fractions but with slight differences in unit cell parameters. Hydrogen storage properties investigated through pressure-composition-temperature absorption and desorption isotherms at different temperatures revealed that the alloy could absorb 1.5 wt% of hydrogen at room temperature without applying any activation procedure, but full desorption was not obtained. At 473 K, the alloy was able to reversibly absorb and fully desorb 1.1 wt% of hydrogen. After full hydrogenation at 473 K, the initial metallic C14 Laves phases were converted into their respective Laves phase hydrides. Under cycling, the fractions of two C14 Laves phases changed while one of the phases was more active to accommodate the hydrogen atoms. After dehydrogenation at 473 K, the alloy presented a single C14 Laves phase. The microstructural analysis, before and after cycling, showed a very well homogeneous microstructure and good distribution of elements. Highlights: CALPHAD method indicated a high trend to the formation of C14 Laves phases for TiZrNbCrFeNi alloy. As cast TiZrNbCrFeNi alloy showed the presence of two C14 Laves phases. Under cycling, the fractions of two C14 Laves phases changes. TiZrNbCrFeNi alloy reversibly absorb and fully desorb 1.1 wt% of hydrogen at 473 K.